Visceral manipulation intervention in functional dyspepsia with or without gastroesophageal reflux disease: a systematic review - Achmad, Arisandy; Manaf, Haidzir (Intelektual Pustaka Media Utama, 2025)
Functional dyspepsia is a prevalent gastrointestinal disorder characterized by symptoms like early satiety, postprandial fullness, and epigastric pain, affecting individuals with or without gastroesophageal reflux disease (GERD). The aim was to systematically map and summarize the existing literature on visceral manipulation interventions for functional dyspepsia. The systematic review followed rigorous methodology to ensure the validity and reliability of the findings. The study involved electronic searches of four major databases and five stages to review references to screened articles from January 2012 to February 2024. The search terms include